A curated dataset for data-driven turbulence modelling - Ryley McConkey (Nature Portfolio, 2021)
Measurement(s) velocity fields • pressure fields • turbulence fields • related gradients Technology Type(s) numerical simulation Factor Type(s) turbulence model • flow geometry Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.15124857